The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m310686200
|View full text |Cite
|
Sign up to set email alerts
|

Signal-induced Ubiquitination of IκB Kinase-β

Abstract: Initiation of the genetic programs for inflammation and immunity involves nuclear mobilization of transcription factor NF-B. This signal-dependent process is controlled in part by the ␤-catalytic subunit of IB kinase (IKK␤), which marks IB␣ and other cytoplasmic inhibitors of NF-B for proteolytic destruction. The catalytic activity of IKK␤ is stimulated by pathologic and physiologic inducers of NF-B, such as the Tax oncoprotein and proinflammatory cytokines. We now report evidence that these NF-B inducers targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 15 publications
9
42
1
Order By: Relevance
“…These results are consistent with an earlier report (21) wherein it was demonstrated that phosphorylation of the activation loop of IKK␤ was inhibited in YopJ-expressing mammalian cells. Our results thus provide a mechanistic basis for the observed inhibition of the canonical NF-B proinf lammatory pathway by YopJ.…”
Section: Yopj Leads To Acetylation Of Mek2supporting
confidence: 83%
“…These results are consistent with an earlier report (21) wherein it was demonstrated that phosphorylation of the activation loop of IKK␤ was inhibited in YopJ-expressing mammalian cells. Our results thus provide a mechanistic basis for the observed inhibition of the canonical NF-B proinf lammatory pathway by YopJ.…”
Section: Yopj Leads To Acetylation Of Mek2supporting
confidence: 83%
“…overexpressed YopP could potentially modify the ubiquitination of several signal transducers that are involved in NF-B activation. This idea is in line with the results of previous publications that have indicated that YopP/YopJ overexpression attenuates the conjugation of cellular proteins with ubiquitin-like SUMO-1 (6) and the ubiquitination of IKK␤ (46). This could give reason to speculations that YopP/YopJ may impair cellular signaling by antagonizing the ubiquitin modification of several critical signal transducers.…”
Section: Yopp Overexpression Modifies Traf6 and Nemo Polyubiquitinationsupporting
confidence: 77%
“…A similar effect of YopP/YopJ has been previously reported on the ubiquitination of IKK␤ (46) and on nonspecified cellular proteins modified with the ubiquitin-like molecule SUMO-1 (6). These results were ascribed to the putative cysteine protease activity of YopP/YopJ, which could mediate cleavage of ubiquitin-like molecules (6,46). However, we could not reveal a reliable effect of YopP on the ubiquitination of TRAF6, NEMO, or TAB2 in Yersinia-infected cells (data not shown).…”
Section: Discussioncontrasting
confidence: 39%
“…Nuclear factor-kB inducers target IKKb for conjugation to ubiquitin in mammalian cells. Carter et al (2003) proposed that T loop phosphorylation at Ser177/Ser181 generates a conditional ubiquitintargeting signal in IKKb by a post-translational mechanism. Increases in accumulation of multiubiquitin after 30 mins of tFCI may show the ubiquitination of the IKK complex.…”
Section: Discussionmentioning
confidence: 99%